Kinerja Keuangan Kabupaten Belitung Timur: Kontribusi Dan Efektivitas Hasil Pengelolaan Kakayaan Daerah Yang Dipisahkan Sebagai Sumber Pendapatan Asli Daerah - Awliya Aqdas; Nizwan Zukhri; Dony Yanuar (Universitas Bangka Belitung, 2021)
The research aims to analyze the contribution and effectiveness as well as influence of the result of thesegregated asset management as local own-source revenue. The method used was descriptive statistics with ratioanalysis and simple linear regression analysis. The data used were secondary in the form of the regional incomereport of East Belitung Regency from 2015-2019. The result showed that the average contribution of the segregatedregional asset management is 3.34 persen that classified as very low. The average effectiveness ratio is 100.08persen which is classified as very effective. The simple linear regression test result showed that the contribution ofthe segregated regional asset management has a positive and significant effect on the local own-source revenue ofthe East Belitung Regency.